The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/2013wr014107
|View full text |Cite
|
Sign up to set email alerts
|

On modeling the paleohydrologic response of closed‐basin lakes to fluctuations in climate: Methods, applications, and implications

Abstract: Climate reconstructions using tree rings and lake sediments have contributed significantly to the understanding of Holocene climates. Approaches focused specifically on reconstructing the temporal water-level response of lakes, however, are much less developed. This paper describes a statistical correlation approach based on time series with Palmer Drought Severity Index (PDSI) values derived from instrumental records or tree rings as a basis for reconstructing stage hydrographs for closed-basin lakes. We use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
(129 reference statements)
0
6
0
Order By: Relevance
“…Due to the sensitivity of lakes, especially closed systems, to climate change, there has been ongoing research on lakes as sentinels or indicators of climate change [9,[61][62][63][64]. Paleoarchives concealed in lake sediments have been used for decades to assess the state of past climates worldwide [65] and in Eurasia [66][67][68][69].…”
Section: Effects Of the Global Circulation Climate Change And Local mentioning
confidence: 99%
“…Due to the sensitivity of lakes, especially closed systems, to climate change, there has been ongoing research on lakes as sentinels or indicators of climate change [9,[61][62][63][64]. Paleoarchives concealed in lake sediments have been used for decades to assess the state of past climates worldwide [65] and in Eurasia [66][67][68][69].…”
Section: Effects Of the Global Circulation Climate Change And Local mentioning
confidence: 99%
“…As discussed in the introduction, the concept of a response time or time constant is well developed in relation to the theory of groundwater flow and lakes (e.g., Liu and Schwartz [14]). In practice, the time required for hydraulic heads in a flow system to readjust to a perturbation can be determined from a set of measurements, for example, from water-level measurements in a piezometer [1] or in a lake [12].…”
Section: Time Lag Calculationmentioning
confidence: 99%
“…In either approach, the response time is defined on the basis of a characteristic associated with the mathematical function that fits the time series. Hvorslev [1], as well as others, e.g., [14,23], found that an exponential function works well. Equation (1) is of that form [23], ( ) ( )…”
Section: Time Lag Calculationmentioning
confidence: 99%
See 2 more Smart Citations